Filming the end of the Holocaust : allied documentaries, Nuremberg and the liberation of the Concentration Camps - Michalczyk, John J. (2014)
Introduction: Prelude to Nuremberg : the Allies seek justice – The US Signal Corps encounters atrocities – The British liberation of Bergen-Belsen : memory of the camps (1945/1985) – The Soviets en route to Nuremberg – Film as visual documentation at the Nuremberg trials – The French connection to Nuremberg – Post-Nuremberg – Epilogue – Notes – Chronology – Holocaust film bibliography – Nuremberg trials bibliography – Filmography..